Proyecto fotográfico: construcción de la narrativa visual del fotolibro “Lenguaje del silencio” - Roca Sánchez, Janet Carolina (2020)
Language of silence is a photographic series which creates a visual and poetic narrative between nudes and nature or objects elements. It aims to communicate irrational ideas and state of emotions that are behind two well-known eating disorders: anorexia and bulimia. To achieve that, I have resorted to personal memory and experience. The creative process occurs because of a previous investigation of diverse academic books and interview with a psychologist. Through photography, we explore topics such as physical dysmorphia, the weakening of the body and the family environment, as well as polarization and catastrophism, polarized thinking, etc.